1999
DOI: 10.1902/jop.1999.70.12.1449
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Findings and Systemic Antibody Responses to Oral Microorganisms in Behçet's Disease

Abstract: Our data indicate that the patients with Behçet's disease generally exhibit clinical findings of established periodontal disease. Decreased antibody responses to early colonizers of both supra- and subgingival plaque were observed along with the elevation in antibody levels to A. actinomycetemcomitans. These results suggest that the bacterial plaque ecology and/or immune responses to these microorganisms may be affected in Behçet's disease which could lead to changes in the expression of periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 43 publications
3
35
0
Order By: Relevance
“…2. VOL. 15,2008 AGE, ORAL DISEASE, AND IMMUNITY IN NONHUMAN PRIMATES 1071 pected, with minimal previous evidence of this type of response except that reported in obese children and adolescents (86) and a general concept of a lack of systemic challenge in children in the absence of clinical changes, but it is consistent with the maturation of host responses in young animals that have to cope with a range of environmental challenges to naïve mucosal surfaces. Testing this concept, we compared these systemic responses in young animals housed under standard conditions with those in comparably aged SPF monkeys.…”
Section: Fig 5 Serumsupporting
confidence: 64%
See 2 more Smart Citations
“…2. VOL. 15,2008 AGE, ORAL DISEASE, AND IMMUNITY IN NONHUMAN PRIMATES 1071 pected, with minimal previous evidence of this type of response except that reported in obese children and adolescents (86) and a general concept of a lack of systemic challenge in children in the absence of clinical changes, but it is consistent with the maturation of host responses in young animals that have to cope with a range of environmental challenges to naïve mucosal surfaces. Testing this concept, we compared these systemic responses in young animals housed under standard conditions with those in comparably aged SPF monkeys.…”
Section: Fig 5 Serumsupporting
confidence: 64%
“…Blood was collected from all animals, serum was prepared, and levels of immunoglobulin G (IgG) antibodies to seven oral bacteria were evaluated using an enzyme-linked immunosorbent assay (ELISA) as we have described previously (14,15). Briefly, Campylobacter rectus, Fusobacterium nucleatum, Aggregatibacter actinomycetemcomitans, Prevotella intermedia, Treponema denticola, Tannerella forsythia, and Porphyromonas gingivalis were grown under anaerobic conditions in mycoplasma broth base with the addition of appropriate additives as we have reported previously (23).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, antibiotics alone (aimed at Chlamydia pneumoniae or Helicobacter pylori, germs uncommon in periodontitis) failed to favorably alter the course of ischemic heart disease (Andraws, Berger, and Brown, 2005). Several infl ammatory diseases have been reported to be associated with severe periodontal disease such as Behcet disease (Akman et al 2007;Celenligil-Nazliel, Kansu, and Ebersole, 1999). None of our subjects had identifi ed active infl ammatory disease at inclusion.…”
Section: Discussionmentioning
confidence: 86%
“…In a recent study, Mumcu et al, (2006) have shown that oral health-related quality-of-life assessments were impaired in patients with BD and associated with disease activity and treatment modalities. Previous studies demonstrated that periodontal scores were higher in patients with BD than the healthy subject (Nakae et al, 1981;Celenligil-Nazlıel et al, 1999;Mumcu et al, 2004;Akman et al, 2007;Karaçaylı et al, 2009;Arabacı et al2009). Also, it has been speculated that BD might develop after the periodontitis and advenced periodontal disease may represent a risk factor for severe organ involvement (Akman et al, 2007).…”
Section: Relationship Between Periodontal Parameters and Behçet's Dismentioning
confidence: 92%